MIRABE: GUIDELINES FOR REPLICATING AUTOMATION IN PUBLIC SCHOOL LIBRARY NETWORKS - Jakeline Farias Souza (Artefactum - revista de estudos interdisciplinares, 2026)
This article presents the Integrated Model for Replicating School Library Automation (MIRABE), a proposal derived from a case study on the implementation of the Pergamum Library Management System in a public school library in Joinville, Santa Catarina, Brazil. The model results from triangulation among a questionnaire administered to 100 participants, ten semi-structured interviews, participant observation, and document analysis. Its purpose is to guide diagnosis, planning, implementation, monitoring, and evaluation of future automation initiatives without reducing replication to reproducing software or pilot routines. MIRABE comprises six interdependent dimensions: diagnosis and institutional readiness; infrastructure and operational continuity; training and change management; data quality and governance; governance, phased implementation, and monitoring; and pedagogical appropriation, mediation, and user education. Its operational cycle includes diagnosis, preparation, technical-operational implementation, stabilization, pedagogical appropriation, and evaluation for continuity or expansion. Decision criteria and process, product, and use indicators are proposed. The study concludes that sustainable automation depends on balancing infrastructure, data, people, governance, processes, and pedagogical appropriation. MIRABE is presented as an analytical generalization that requires multicenter validation before being treated as a consolidated protocol.